Voters' Political Preferences for Female Legislative Member Candidates in Tulungagung Regency - Munawir, Yusron; Setiarni Putri, Taniya (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
The number of women's representation in seats in the Tulungagung Regency Regional People's Representative Council so far is still low, only 12% in the 2019 Election and 14% in the 2024 Election, while the percentage of female legislative candidates elected in the 2024 DPR RI Election reached 22.06%. Therefore, efforts need to be made to increase the number of women's representation in the Tulungagung DPRD by looking at the political preferences of voters in Tulungagung. This research aims to determine voters' political preferences for female legislative candidates in Tulungagung Regency and their relevance to election results. This research is mixed quantitative-qualitative research, with quantitative data analysis techniques followed by qualitative data analysis. Data collection through questionnaires and documentation. The results of the research found voters' political preferences for female legislative candidates in Tulungagung, considering that female legislative candidates are trusted to channel the aspirations of women and children, organizational abilities, reciprocity, high level of education, age maturity, similarity of political parties, and candidate popularity. There is a congruence in political preferences for the majority of female legislative candidates elected in Tulungagung in the 2019 and 2024 elections.